GEOGRAPHICAL EXPANSION OF CANINE VISCERAL LEISHMANIASIS IN RIO DE JANEIRO STATE, BRAZIL - SILVA, Denise Amaro da; MADEIRA, Maria de Fátima; FIGUEIREDO, Fabiano Borges (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Visceral Leishmaniasis (VL) is a vector-borne disease that affects humans, and domestic and wild animals. It is caused by the protozoan Leishmania (Leishmania) infantum (syn = Leishmania chagasi). The domestic dog (Canis familiaris) is considered the main reservoir of the etiologic agent of VL in domestic and peridomestic environments. In the past three years, although control actions involving domestic dogs are routinely performed in endemic areas of the Rio de Janeiro State, new cases of canine visceral leishmaniasis (CVL) have been reported in several municipalities. The objective of this short communication was to describe the geographical expansion of CVL in the Rio de Janeiro State, Brazil, through its reports in the scientific literature and studies performed by our group. From 2010 to 2013, autochthonous and allochthonous cases of CVL were reported in the municipalities of Mangaratiba, Marica, Niteroi, Barra Mansa, Cachoeiras de Macacu, Volta Redonda, Resende and Rio de Janeiro. These reports demonstrate that CVL is in intense geographical expansion around the state; therefore, a joint effort by public agencies, veterinarians and researchers is needed in order to minimize and/or even prevent the dispersion of this disease.